Hubungan Harga Saham, Struktur Kepemilikan, Ukuran Perusahaan, dan Profitabilitas dengan Tindakan Perataan Laba - Dita Sucilarasati; Yanuar Nanok Soenarno (Media Ilmiah Akuntansi, 2021)
This study aims to identify the factors that have a relationship with income smoothing actions in manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2018. These factors include stock prices, ownership structure, company size, and profitability. Result of this study are, stock price and profitability have a significant relationship with income smoothing actions, while the ownership structure and company size do not have a significant relationship with income smoothing actions.